DAKWAH KENABIAN DAN KONSTRUKSI MASYARAKAT KHAYALAN - ISHAK HARYANTO (Mudabbir: Jurnal Manajemen Dakwah, 2021)
Abstract The journey of the Prophet's da'wah as an arena to build a humanitarian system that is mutually acceptable and recognizes the values ??of human equality in the social system is still a deviation, even though life must embrace each other, accept unconditionally and respect human values. Acceptance between human beings seems to have become a deviation and even become a collective amnesia in social life. This collective amnesia is present in human life without realizing that we live in it so that acceptance for humans as a form of hablumminannas is like the construction of an imaginary society. The construction of an imaginary society had occurred in Medina as a social institution in the journey of prophetic da'wah. This happens as a living system process; a process of building its identity as a social system in building the ideal society that ever existed on this earth. The Medina community is a society based on a collective agreement that is contained in a charter, commonly known as the Medina charter, written above the interests of all groups, so that it can become a radical turning point for civilization to completely overhaul the values, symbols, and structures of society that have become acute. The Medina community is a society that results from a completely new social order so that it becomes a normal community identity. Be a role model when compared to neighboring areas at that time. Relationships between groups are built based on the breath of acceptance between others, because of the awareness of the similarity of nature and dignity as human beings. Why Medina is called the identity of a normal social system, none other than because of intersubjectivity; Human acceptance that is built from all components of the social system is always in communication and mutual acceptance.